Aboriginal health and Aboriginal deaths in custody - McDonald, David (David Neil), 1946- (Research discussion paper (Australian Institute of Aboriginal and Torres Strait Islander Studies), 1996)
Reviews the findings of the Royal Commission into Aboriginal Deaths in Custody, with particular reference to recommendations relating to Aboriginal health; trends in deaths in custody; although implementation of the Commission's recommendations has resulted in a reduction of Aboriginal deaths in police lockups, overcrowding in prisons has negated the improvements made in Australian prisons.